The Effect of Exercise Intervention on Non-Specific Neck Pain and Head and Neck Angles Among Adult Smartphone Users - Sara Tabanfar; Seyvan Sobhani; Ali Safari Variani; Sakineh Varmazyar (Journal of Health Sciences and Surveillance System)
Background: This study aimed to investigate the effect of exercise intervention on non-specific neck pain and head and neck angles among adult smartphone users.Methods: This interventional study was conducted among 84 adults divided into experimental and control groups. Data were collected using a demographic questionnaire and the Visual Analogue Scale (VAS). Craniovertebral angle (CVA), head flexion angle (HFA), gaze angle (GA), and forward head position (FHP) were determined from photographs analyzed with Kinovea software. The corrective exercises included 10 exercises targeting the neck muscles, including flexors, deep flexors, scapulothoracic muscles, and stretching of both left and right neck muscles. The experimental group performed these exercises for 12 weeks, with five weekly sessions lasting 15 minutes each. Research variables were re-measured immediately after the intervention.Results: 45.3% of the experimental group reported moderate neck pain severity before the intervention. Following the intervention, 33.3% of the experimental group reported no neck pain. The severity of neck pain significantly improved in the experimental group after the intervention (t=8.08, P=0.004). The greatest angle improvement was observed in GA, with a mean increase of 20.44° in the experimental group after three months (t=12.49, P=0.003). HFA (t=6.52, P=0.009) and FHP (t=12.74, P=0.007) significantly decreased in the experimental group postintervention. Additionally, CVA showed a statistically significant increase in the experimental group (t=-11.75, P=0.004).Conclusion: Over half of the experimental group reported reduced neck pain severity after the exercise intervention. Three months of corrective exercises significantly decreased HFA and GA while increasing CVA in the experimental group by more than 10 degrees.